AKIBAT HUKUM PERBEDAAN PENYELESAIAN PERSELISIHAN HUBUNGAN KERJA TERHADAP UNDANG-UNDANG CIPTA KERJA - Jatmiko, Bayu Priyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Disputes or dispute cases often occur between workers/laborers and employers. So the government established the Industrial Relations Court (PHI) as the main institution for resolving disputes between workers and liberal employers. The course of the problem is entirely in the hands of the litigants. So the purpose of this research is for workers/labourers, trade unions, and employers to know the differences from the Termination of Employment. Policies according Constitution number 13 year of 2003 concerning Emploiment and constitution number 11 year of 2020 in a precise and binding manner. Using normative research with the aim of answering scientifically based issues. From this research, the researcher offers results for workers/laborers of legal protection from the labor system. 1) protection of wages, 2) protection of workers' safety and health, 3) and protection of workers' basic rights